Environmental dilemmas revisited: structural consequences from the angle of institutional ergonomics - Martin Beckenkamp (Max Planck Institute for Research on Collective Goods, 2009)
The structure of a social dilemma lies behind many environmental problems. Mingling temporal aspects of resources with the structure of the social dilemma often leads to wrong conclusions. Therefore, it is worth analytically separating temporal aspects from structural aspects of the dilemma. This article concentrates solely on the structural aspects of the dilemma and the grades of complexity with respect to the number and stakes of the people involved, as well as the asymmetry of endowments and the salience of the optimal use of the resource in order to come close to the welfare optimum. Dilemmas with sufficient complexity are extremely vulnerable to individual defectors, and therefore institutions are necessary for the solution of the dilemma. Consequently, research in environmental psychology should not only target the individuals, but focus on institutional design with respect to (1) the structural diagnosis of environmental dilemmas; (2) methods that provide an insight into the structural problem of environmental dilemmas; (3) the impact of institutions on internalizing norms; and (4) the impact of structural knowledge about the dilemma of accepting institutions that help to solve the environmental dilemma. In analogy to software-ergonomics, psychology should initiate research in institutional ergonomics that helps to create addressee-friendly institutions.
Keywords: 330; Social dilemma; Resource dilemma; Game theory; environment; institutional design; Umweltökonomik; Allmenderessource; Gefangenendilemma; Institutionalismus; Reziprozität; Theorie